A Chemical Approach to Optimizing Bioactive Glass Dental Composites. (February 2019) - Aponso, S.; Ummadi, J.G.; Davis, H.; Ferracane, J.; Koley, D.
The chemical microenvironment surrounding dental composites plays a crucial role in controlling the bacteria grown on these specialized surfaces. In this study, we report a scanning electrochemical microscopy (SECM)–based analytic technique to design and optimize metal ion-releasing bioactive glass (BAG) composites, which showed a significant reduction in biofilm growth. SECM allows positioning of the probe without touching the substrate while mapping the chemical parameters in 3-dimensional space above the substrate. Using SECM and a solid-state H + and Ca 2+ ion-selective microprobe, we determined that the local Ca 2+ concentration released by different composites was 10 to 224 µM for a BAG particle size of <5 to 150 µm in the presence of artificial saliva at pH 4.5. The local pH was constant above the composites in the same saliva solution. The released amount of Ca 2+ was determined to be maximal for particles <38 µm and a BAG volume fraction of 0.32. This optimized BAG-resin composite also showed significant inhibition of biofilm growth (24 ± 5 µm) in comparison with resin-only composites (53 ± 6 µm) after Streptococcus mutans bacteria were grown for 3 d in a basal medium mucin solution. Biofilm morphology and its subsequent volume, as determined by the SECM imaging technique, was (0.59 ± 0.38) × 10 7 µm 3 for BAG-resin composites and (1.29 ± 0.53) × 10 7 µm 3 for resin-only composites. This study thus lays the foundation for a new analytic technique for designing dental composites that are based on the chemical microenvironment created by biomaterials to which bacteria have been exposed.